Evaluation of the Laparoscopic Cystectomy for Endometrioma in Women of the Reproductive Age - Berna Dilbaz; Caner Kose; Yaprak Engin Ustun; Sule Atalay Mert (Tropical Health and Medical Research, 2023)
Aim of the study is to evaluate the pregnancy outcome and recurrence of the disease in patients with endometrioma. All patients who underwent laparoscopic surgery for endometrioma between January 2017- 2020 in Etlik Zubeyde Hanim Women Health Training and Research Hospital, had a stage 3-4 disease, and met the inclusion criteria were evaluated. The exclusion criteria were; being menopausal, having laparotomy for endometrioma surgery, or presence of concomitant leiomyoma. The post-operative reproductive outcome and the recurrence rate were evaluated. Out of the 97 patients recruited, 57 (58.8%) were followed up for infertility, while the remaining forty had no desire for future pregnancy. Sixty-seven patients had elective surgery, and 30 (30.9%) underwent emergency surgery. Pregnancy was achieved in 18 (31.5%) within 3-18 months (8.94Â±4.54) after surgery, of which seven (38.8%) were spontaneous pregnancies while 11 had pregnancy through assisted reproductive techniques. The live birth rate was 88.8%, thirteen term delivery. Out of 97 patients, only four (4,1%) had recurrent endometrioma. The total pregnancy rate was high in the secondary infertile group (44.8%-17.8%), and the IVF pregnancy rate (60%) was high in the primary infertile group. Endometrioma surgery can be recommended for selected patients while preserving ovarian tissue.